2021
DOI: 10.3389/fmed.2021.735150
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Arthritis and Metabolic Syndrome: Is There a Role for Disease Modifying Anti-Rheumatic Drugs?

Abstract: Although psoriatic arthritis (PsA) primarily leads to joint and skin damage, it is associated with higher prevalence of metabolic syndrome (MetS) and its components, namely hypertension, dyslipidemia, obesity, and type II diabetes. Additionally, chronic inflammation is known to aggravate these cardiometabolic factors, thus explaining the enhanced cardiovascular (CV) morbidity and mortality in RA. Furthermore, emerging evidence suggest that some risk factors can fuel inflammation, thus pointing to a bidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 111 publications
1
2
0
Order By: Relevance
“…A sex-adjusted linear regression model confirmed that patients with PsA were significantly taller (p = 0.015), weighed more (p = 0.001), and thus had higher BMI (p = 0.01) than patients with RA. The finding of higher weight, BMI, and prevalence of hypertension in PsA patients compared with RA patients is consistent with the high incidence of CV risk factors among patients with PsA reported in literature [21]. Participants in the two disease groups were comparable regarding past medical history, but significantly more patients in the RA group were smokers, whereas significantly more patients in the PsA group had comorbid hypertension (Table 1).…”
Section: Study Participantssupporting
confidence: 86%
“…A sex-adjusted linear regression model confirmed that patients with PsA were significantly taller (p = 0.015), weighed more (p = 0.001), and thus had higher BMI (p = 0.01) than patients with RA. The finding of higher weight, BMI, and prevalence of hypertension in PsA patients compared with RA patients is consistent with the high incidence of CV risk factors among patients with PsA reported in literature [21]. Participants in the two disease groups were comparable regarding past medical history, but significantly more patients in the RA group were smokers, whereas significantly more patients in the PsA group had comorbid hypertension (Table 1).…”
Section: Study Participantssupporting
confidence: 86%
“…Both treatment with MTX and TNFi have previously been linked to improved insulin sensitivity ( 45 , 46 ). Moreover, because no patients were treated with systemic corticosteroids during the trial, we do not think that DMARDs are the likely cause of the elevated plasma glucose levels observed in the failure group.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to CV risk factors associated with PsA, the available evidence shows that metabolic comorbidities, obesity in particular, are involved [14,15,35]. The distinction in terms of CV risk profile from RA, despite the fact that both diseases are characterized by chronic inflammation, has been previously addressed [8,9,35,36]. It has been pointed out that, contrary to RA where systemic inflammation appears to contribute directly to the increased CV risk, in PsA traditional risk factors, including adiposity and MetS, are major contributors to the CV risk [8,35,37].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated risk of CV and cerebrovascular events compared to the general population has also been reported for psoriatic arthritis (PsA) [2,7]. The increased CV risk associated with RA and other chronic inflammatory conditions is likely caused by the complex interplay of traditional CV risk factors, chronic systemic inflammation, and side effects related to the use of certain antirheumatic medications [8,9]. Although a similar figure has been proposed for PsA, to what extent these arthropathies differ is yet to be clarified.…”
Section: Introductionmentioning
confidence: 94%